Identification of Botanical Biomarkers in Argentinean Diplotaxis Honeys: Flavonoids and Glucosinolates - Truchado, Pilar (2010)
To select and establish floral biomarkers of the botanical origin ofDiplotaxis tenuifoliahoneys, the flavonoids and glucosinolates present in bee-deposited nectar collected from hive combs (unripe honey) and mature honey from the same hives fron which the unripe honey samples were collected were analyzed by LC-UV-PAD-ESI-MSn. Glycosidic conjugates of the flavonols quercetin, kaempferol, and isorhamnetin were detected and characterized in unripe honey.D. tenuifoliamature honeys contained the aglycones kaempferol, quercetin, and isorhamnetin. The differences between the phenolic profiles of mature honey and freshly deposited honey could be due to hydrolytic enzymatic activities. Aliphatic and indole glucososinolates were analyzed in unripe and mature honeys, this being the first report of the detection and characterization of glucosinolates as honey constituents. Moreover, these honey samples contained different amounts of propolis-derived flavonoid aglycones (1765−3171 μg/100 g) and hydroxycinnamic acid derivatives (29−1514 μg/100 g). Propolis flavonoids were already present in the freshly deposited nectar, showing that the incorporation of these compounds to honey occurs at the early steps of honey production. The flavonoids quercetin, kaempferol, and isorhamnetin and the glucosinolates detected in the samples could be used as complementary biomarkers for the determination of the floral origin of ArgentineanDiplotaxishoneys.